1999
DOI: 10.5144/0256-4947.1999.27
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Stroke in Hofuf, Saudi Arabia

Abstract: Background: Stroke is a common neurological disorder that is encountered in most hospitals in both developed and developing countries. This two-year study was designed to show the characteristics of the problem at the King Fahad Hospital, Hofuf, Saudi Arabia. Patients and Method: This was a prospective study of all Saudi stroke patients admitted to the medical wards in the study period. All patients were assessed individually by one of the two available neurologists. Data was collected on pre-designed protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 29 publications
11
36
6
Order By: Relevance
“…Lower rates are found in developed countries: 23% in Norway and 26% in Japan (Turin et al, 2010;Ihle-Hansen et al, 2012). Moreover, the frequency of AF (18.5%) among the stroke patients in our sample is high compared with values recorded in other Arab countries (El-Sayed et al, 1999;Hamad et al, 2001;Ashkanani et al, 2013;Al-Asadi and Habib, 2014), but lower than the frequency in Western countries, where the population is older; AF is indeed known to increase with age (Ihle-Hansen et al, 2012). With regard to the ischemic stroke subtypes defined according to the modified TOAST classification criteria, LA was the most common, accounting for 53.5% of all ischemic strokes, a rate higher than in published data.…”
Section: Discussioncontrasting
confidence: 48%
“…Lower rates are found in developed countries: 23% in Norway and 26% in Japan (Turin et al, 2010;Ihle-Hansen et al, 2012). Moreover, the frequency of AF (18.5%) among the stroke patients in our sample is high compared with values recorded in other Arab countries (El-Sayed et al, 1999;Hamad et al, 2001;Ashkanani et al, 2013;Al-Asadi and Habib, 2014), but lower than the frequency in Western countries, where the population is older; AF is indeed known to increase with age (Ihle-Hansen et al, 2012). With regard to the ischemic stroke subtypes defined according to the modified TOAST classification criteria, LA was the most common, accounting for 53.5% of all ischemic strokes, a rate higher than in published data.…”
Section: Discussioncontrasting
confidence: 48%
“…In the current study (67.3±5.3) years was the mean age of stroke patients which is concordant with many studies done in developing countries (El Sayed et al, 1999;Cheung et al, 2007;Dalal et al, 2005) also with AlAsadi et al, studies which is done in Basrah in Iraq in 2014Iraq in (2014.More than half of the patients was within the age group 60-69 and the male was more predominant than female which is similar to that found by a previous study done in Iraq by Sulaiman, in 2002Sulaiman, in (2002, Moreover it is similar to the Minelli study in Brazil in 2007Brazil in (2007 and with Mihalka in 2001in West Ukrain (2001. More than 4/5 th (80.7%) of the stroke patients in the present study were ischemic type and the rest was hemorrhagic consistent with that registered by Hamad et al, in Qatar in 2001(2001 were 80% of the stroke patients was ischemic type.…”
Section: Resultssupporting
confidence: 92%
“…More than 4/5 th (80.7%) of the stroke patients in the present study were ischemic type and the rest was hemorrhagic consistent with that registered by Hamad et al, in Qatar in 2001(2001 were 80% of the stroke patients was ischemic type. Also it is similar to that registered in a study done in Saudia Arabia by El-Sayed (El Sayed et al, 1999) in 1999. This may be explained by that most Arabic Gulf people are adopting Western lifestyle and dietary habits, including increased fat intake, cigarette smoking and decreased physical activity.…”
Section: Resultssupporting
confidence: 91%
“…Thirty-one articles were included from the following Arab countries: Saudi Arabia (n=16) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], Qatar (n=4) [21][22][23][24], Libya (n=3) [25][26][27], Kuwait (n=2) [28,29], Jordan (n=1) [30], United Arab Emirates (n=1) [31], Bahrain (n=1) [32], Tunisia (n=1) [33], Iraq (n=1) [34] and Sudan (n=1) [35] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study from Saudi Arabia showed an equal ratio of males to females [18] and another from Kuwait showed a slightly higher female preponderance at 51.7% [28]. The clinical series showed a mean age of stroke within the sixth and seventh decade (varying from 58.5 to 63) [6,15,18,21,22,[29][30][31].…”
Section: Sex and Agementioning
confidence: 99%